Avaliação de compostos com atividade antioxidante de extratos de Açaí de Juçara (Euterpe edulis Mart.) e aplicação em sorvete diet - Silva, Letícia Dangui da (2018)
Açaí Juçara (Euterpe edulis Mart.) is a tropical fruit, found in the Atlantic Forest Brazilian, known for its high nutritional value and excellent antioxidant (AA) activity. The objective of this work was to optimize the extraction process, to evaluate the profile of the phenolic compounds with AA and to apply the lyophilized extract of Açaí Juçara (ALE) in diet ice cream formulations added with enzymes lactase (LE) and transglutaminase (TE). Six formulations of diet ice cream were prepared to assess the ability of ALE to inhibit lipid oxidation: F1 (ALE + LE + TE), F2 (ALE), F3 (ALE + LE), F4 (LE + TE), F5 (LE + TE + BHT) and F6 (ALE + TE). In this study, the reducing sugar content, overrun, texture and calorimetry were also evaluated in the ice cream. The content of total phenolic compounds and the profile of phenolic compounds were determined by the Folin-Ciocateau method and high performance liquid chromatography (HPLC), respectively. The lipid oxidation of the ice cream was evaluated by thiobarbituric acid reactive substances (TBARS) monthly for 90 days. The reducing sugar content was determined by the Somogy-Nelson method, the texture was evaluated by Texture Profile Analysis (TPA), while the overrun was evaluated by the percentage of air incorporation in the ice cream. High content of total phenolic compounds was found in the ALE (345.32 mg EAG.g-1: Equivalent in gallic acid), with salicylic acid being the major phenolic compound (166.89 μg/g). The extract presented strong antioxidant capacity and inhibited 24.57% of lipid oxidation in F1 after 90 days of storage, in comparison to the F4 control. In the analysis of overrun, all formulations presented yield above 40%. The total color difference of the ice creams after 15 days of storage revealed that all formulations had a visible color difference to the naked eye. The addition of ALE and enzymes provided an innovative product with technological and functional properties suitable for a diet ice cream.